Mental health issues and illness and substance use disorder (non-)disclosure to a supervisor: a cross-sectional study on beliefs, attitudes and needs of military personnel - Elbert Geuze; N Greenberg; Fenna Leijten; Jaap van Weeghel; Rebecca Bogaers; Evelien Brouwers; D van de Mheen; A D Rozema (BMJ Open)
Objectives Research suggests that military personnel frequently delay disclosing mental health issues and illness (MHI), including substance use disorder, to supervisors. This delay causes missed opportunities for support and workplace accommodations which may help to avoid adverse occupational outcomes. The current study aims to examine disclosure-related beliefs, attitudes and needs, to create a better understanding of personnel’s disclosure decision making.Design A cross-sectional questionnaire study among military personnel with and without MHI. Beliefs, attitudes and needs regarding the (non-)disclosure decision to a supervisor were examined, including factors associated with (non-)disclosure intentions and decisions. Descriptive and regression (logistic and ordinal) analyses were performed.Setting The study took place within the Dutch military.Participants Military personnel with MHI (n=324) and without MHI (n=554) were participated in this study.Outcome measure (Non-)disclosure intentions and decisions.Results Common beliefs and attitudes pro non-disclosure were the preference to solve one’s own problems (68.3%), the preference for privacy (58.9%) and a variety of stigma-related concerns. Common beliefs and attitudes pro disclosure were that personnel wanted to be their true authentic selves (93.3%) and the desire to act responsibly towards work colleagues (84.5%). The most reported need for future disclosure (96.8%) was having a supervisor who shows an understanding for MHI. The following factors were associated both with non-disclosure intentions and decisions: higher preference for privacy (OR (95% CI))=(1.99 (1.50 to 2.65)intention, 2.05 (1.12 to 3.76)decision) and self-management (OR (95% CI))=(1.64 (1.20 to 2.23)intention, 1.79 (1.00 to 3.20)decision), higher stigma-related concerns (OR (95% CI))=(1.76 (1.12 to 2.77)intention, 2.21 (1.02 to 4.79)decision) and lower quality of supervisor–employee relationship (OR (95% CI))=(0.25 (0.15 to 0.42)intention, 0.47 (0.25 to 0.87)decision).Conclusion To facilitate (early-)disclosure to a supervisor, creating opportunities for workplace support, interventions should focus on decreasing stigma and discrimination and align with personnels’ preference for self-management. Furthermore, training is needed for supervisors on how to recognise, and effectively communicate with, personnel with MHI. Focus should also be on improving supervisor–employee relationships.